ANALYSIS PURCHASE INTENTION OF MEN'S SKINCARE: THE ROLE OF CONTENT MARKETING, PRODUCT INNOVATION, AND PERCEIVED VALUE AS PREDICTORS - Vidyanata, Deandra; Kusuma, Rr. Chusnu Syarifa Diah; Septiani, Emilia; Rane, Melvin Krisdiana Djami (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
In an increasingly advanced digital era, content marketing has become an important tool for reaching consumers and building strong relationships with them. Informative, relevant and interesting content can increase consumer awareness and interest in skincare products. This research aims to analyze men's skincare purchase intention by focusing on the role of content marketing, product innovation, and perceived value as the main predictors. This research methodology uses a quantitative approach by collecting data through questionnaires distributed to male respondents who use skincare products. Data analysis was carried out using regression techniques to test the relationship between the variables studied. The sample used as respondents was 170 people. The research results show that content marketing, product innovation, perceived value have a positive and significant effect on purchase intention. The results of this research have important implications for companies that market men's skincare products, namely that effective content marketing must be a top priority, because relevant and interesting content can significantly increase consumer awareness and interest. Then product innovation must continue to be improved to meet the ever-changing needs and preferences of consumers. In addition, companies must ensure that consumers perceive high value from their products, both through superior quality, reasonable prices, and emotional and social benefits.